Sonosyntactics : selected and new poetry of Paul Dutton - Dutton, Paul, 1943- (Wilfrid Laurier University Press, 2015)
"Sonosyntactics" introduces the reader to Paul Dutton s poetry, ranging from lyrics, prose poems, and visual work to performance texts and scores.?"Sonosyntactics"?gathers a representative selection of his most significant and characteristic poetry together with a selection of uncollected new work."--Publisher.
Keywords: Canadian poetry -- 21st century.; FICTION / General; Canadian poetry; 2000-2099